Knowledge of our incorporated America: research and intermedial creation based on the philosophy of culture of Günter Rodolfo Kusch: Investigación y creación intermidial a partir de la filosofia de la cultura de Günter Rodolfo Kusch (Revista NUPEART, 2025)
Revisiting aesthetic categories from Günter Rodolfo Kusch's(1922-1979)philosophy, this article discusses the research conducted by the Research Group “FiloMove: Philosophies, Arts, and Aesthetics of Latin America”in the process of creating the show "Latin American Station: tribute to Rodolfo Kusch." The project aimed to reflect on intermedial experimentation, creating cross-border fields between knowledge and techniques derived from Latin American popular culture for their application in the training of teachers and artist-researchers in Brazil. Five vectors or media texts were combined: music, dance, theater, audiovisual media, and, as a conceptual innovation, the philosophical essay. In the current debate on intermedialstudies, the philosophy of culture developed by Rodolfo Kusch anticipates some of the propositions regarding the status of the body in philosophical practice as research. The project shows ways to produce new meanings by connecting media texts associated with Latin American values. The research results were shared as an educational performance.
Keywords: intermidiality studies; perforamnce; performance-philosophy; Rodolfo Kusch; Latin America